The evaluation of kindergarten teachers’ preparation to promote oral health among children - Chałas, Renata; Maksymiuk, Paweł; Fajgier, Tomasz (Polish Journal of Public Health, 2014)
Introduction. The problem of high caries prevalence among preschool children has been widely discussed in Poland. Studies show unsatisfactory level of children’s oral health. A reason of this situation could be insufficient health education.Aim. The aim of the study was to evaluate kindergarten teachers’ preparation to promote oral health among children.Material and methods. Ninety-seven preschool teachers from Lublin (96 women and 1 man) participated in the study. Teachers were asked to fill survey forms concerning: oral health education campaigns launched in the kindergarten, meals consumed by kids and basic issues of oral hygiene.Results and discussion. The majority of examined teachers (96.91%) confirmed that oral health education campaigns were executed at their workplace. Significantly less people confirmed execution of fluoridation programs. Half of the subjects (53.61%) rated their knowledge of oral health diseases prevention as good. Passing on the knowledge about oral hygiene during lessons with children was confirmed by 96.91% subjects. A great proportion of the subjects (71.13%) think that launching regular oral health education campaigns among teachers would help to improve oral health level of children.Conclusions. Kindergarten teachers have general, but not expert knowledge of oral health. Trained teachers could play an important role in raising children health status.